The Impact of BPJS Health Post-Claim Refunds on Hospital Administrative Services - Baiq Dian Septina; Sastrawan Sastrawan; Sabar Setiawan (Postgraduate, University of Mataram, 2026)
A high rate of post-claim refunds indicates challenges in the claims administration process, including incomplete documentation, administrative errors, and inconsistencies with BPJS Kesehatan verification standards. These issues may delay claim payments and affect hospital financial and operational performance. This study aimed to analyze the impact of post-claim refunds on hospital administrative services. This study employed a qualitative descriptive approach. Data were collected through in-depth interviews, observations, focus group discussions, and document reviews. Data were analyzed using the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing and verification. The results showed that post-claim refunds from BPJS Kesehatan have significant implications for hospital administrative services. Delays in claim reimbursement disrupt cash flow, reduce financial liquidity, and complicate budget planning. Furthermore, the refund process increases administrative workload, requires intensive coordination among hospital units, and may delay the procurement of facilities, payment of service incentives, and other operational activities. These conditions can affect administrative efficiency and the continuity of healthcare services. In conclusion, post-claim refunds have substantial impacts on hospital administrative and financial management. Strengthening claim verification procedures, improving documentation quality, and enhancing coordination among related units are necessary to minimize refund occurrences and support the sustainability of hospital services